1997
DOI: 10.1046/j.1365-201x.1997.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in pig outer retina in light and darkness

Abstract: In the pig eye, oxygen and glucose consumption in the outer retina are reduced in light compared to the consumption in the dark and most of the glucose consumed is metabolized to lactate both in light and in the dark. In the present study, in order to characterize the metabolism of glucose in the inner retina. Blood was collected from an artery and from a plexus on the optic nerve draining blood from the retina. Arteriovenous concentration differences for glucose, lactate and oxygen were determined. Observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
153
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 16 publications
8
153
2
Order By: Relevance
“…Our findings that MCs do not express PK and that PRs express abundant PKM2 suggested that PRs, and not MCs, are the primary source of Lac. Retinas convert Glc to Lac at a very fast rate (4)(5)(6)(7)13 deficiency causes PR degeneration (27), so we extracted metabolites from mutant and control retinas and quantified them by GC/MS (Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings that MCs do not express PK and that PRs express abundant PKM2 suggested that PRs, and not MCs, are the primary source of Lac. Retinas convert Glc to Lac at a very fast rate (4)(5)(6)(7)13 deficiency causes PR degeneration (27), so we extracted metabolites from mutant and control retinas and quantified them by GC/MS (Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…Aerobic glycolysis accounts for 80-96% of Glc used by retinas (4)(5)(6)(7). Retinas are made up of neurons and glia (8).…”
mentioning
confidence: 99%
“…Of the intracellular isoforms, CA V is expressed in neuronal and glial mitochondria (10), and CA II is highly expressed in oligodendrocytes and in Müller cells in retina (9,15). Of the membrane-bound isoforms in brain, CA IV has been demonstrated on the luminal surface of cortical capillary endothelial cells (16,17) and on neurons and glia in selected regions of brain (18), and CA XIV has been found on neurons and axons in brain tissue (11). Thus, the CA XIV isoform may also be of importance for regulation of neuronal excitability and transport processes in brain.…”
mentioning
confidence: 99%
“…Moreover, the direction of transport is better defined in the retina than in the more complex neuropil of the brain. For example, the flux of lactate has been shown to occur constitutively from the inner to the outer aspect of the retina (18). Other transport processes may shift polarity depending on the metabolic activity.…”
mentioning
confidence: 99%
“…Although dark adaptation is a complex psychovisual function, the most probable reason for this is the high energy demand of the photoreceptor complex, which for proper function is critically dependent upon the oxygen tension in the outer segment of the retina, as shown in animal experiments (Bill & Sperber 1990;Linsenmaier & Braun 1992;Braun et al 1995;Wang et al 1997). As dark adaptometry is a rather simple psychovisual test, far less complicated than ordinary psychometric tests, we chose this sensitive function to study the consequenses of a possibly insufficient microcirculation secondary to polycythemia.…”
Section: Discussionmentioning
confidence: 99%